Situation Report: Hungary, 14 October 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Working Class Becoming More Critical First Details on Hungarians Working at Cierna nad Tisou Importance of Hungarian Chamber of Commerce to Be Increased? Joint Metallurgical Investment with USSR Hungary and Austria Agree on Highway Development Visa Abolished between Hungary and East Germany Can Hungary Suspend Imports of Corn Fodder? New Attempt to Eliminate State Monopoly in Agriculture Collaboration among Agricultural Co-operatives Preferred to Merge Tenth Anniversary of the Hungarian Writers' Union